2019
DOI: 10.1002/ajmg.a.61464
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in individuals with osteogenesis imperfecta in North America: Results from a multicenter study

Abstract: Hearing loss (HL) is an extra‐skeletal manifestation of the connective tissue disorder osteogenesis imperfecta (OI). Systematic evaluation of the prevalence and characteristics of HL in COL1A1/COL1A2‐related OI will contribute to a better clinical management of individuals with OI. We collected and analyzed pure‐tone audiometry data from 312 individuals with OI who were enrolled in the Linked Clinical Research Centers and the Brittle Bone Disorders Consortium. The prevalence, type, and severity of HL in COL1A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…A growing interest has been directed towards the concepts of listening effort and fatigue, social isolation, and depression that are associated with hearing loss [ 37 39 ]. In individuals with OI, hearing loss is more pronounced in mild types and becomes more severe with advancing age [ 37 40 ]. We found more reports of severe fatigue among those adults with mild OI type as compared to those with severe OI type [ 6 ], a finding which might be explained partly by fatigue caused by listening effort.…”
Section: Discussionmentioning
confidence: 99%
“…A growing interest has been directed towards the concepts of listening effort and fatigue, social isolation, and depression that are associated with hearing loss [ 37 39 ]. In individuals with OI, hearing loss is more pronounced in mild types and becomes more severe with advancing age [ 37 40 ]. We found more reports of severe fatigue among those adults with mild OI type as compared to those with severe OI type [ 6 ], a finding which might be explained partly by fatigue caused by listening effort.…”
Section: Discussionmentioning
confidence: 99%
“…Machol et al 31 collected audiometry results from 312 people with osteogenesis imperfecta. They found hearing loss in types I, III and IV combined to be 28%.…”
Section: Resultsmentioning
confidence: 99%
“…Hearing loss is a recognized extra-skeletal manifestation of OI, and the mechanism is thought to involve abnormal mineralization and otosclerosis-like process in the inner ear (23). This has been primarily described in individuals with dominant COL1A1/COL1A2-related OI (23) and has also been reported in some recessive forms of OI (24,25) and in OI mouse models (26,27). Hearing loss may be conductive, sensorineural, or mixed, as well as unilateral or bilateral.…”
Section: Hearing Lossmentioning
confidence: 99%
“…Conductive hearing loss is most frequently found in the pediatric and adolescent populations, while mixed or sensorineural hearing loss are found predominantly in adults (23,24,28). When present, hearing impairment is in the milder range and of adult onset in most patients, with no clear relation to OI type or severity (23); however, one study identified a higher risk of early onset hearing loss in moderate to severe forms of OI (24). The reported prevalence varies across studies; a recent study with a North American cohort of 312 individuals reported hearing impairment in 28% of OI cases (24).…”
Section: Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation